The role of Umkhonto we Sizwe (MK) in the national liberation struggle in South Africa with reference to the rural far northern Transvaal, 1976-1990 - Lesetja, Marepo (Department of Political Studies, 2014)
Includes bibliographical references (leaves 250-275).